2021
DOI: 10.1128/aem.00544-21
|View full text |Cite
|
Sign up to set email alerts
|

Forty Years of Oxalobacter formigenes, a Gutsy Oxalate-Degrading Specialist

Abstract: Oxalobacter formigenes , a unique anaerobic bacterium that relies solely on oxalate for growth, is a key oxalate-degrading bacterium in the mammalian intestinal tract. Degradation of oxalate in the gut by O. formigenes plays a critical role in preventing renal toxicity in animals that feed on oxalate-rich plants. The role of O. formigenes in reducing the risk of calcium oxalate kidney stone disease and oxalate nephropathy in humans is less clear, in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 104 publications
2
38
0
Order By: Relevance
“…While we were not able to sequence the genomes of all Oxalobacter strains, the 16S rRNA gene was used to predict the species that additional strains should be assigned to. These results revealed that SOx4, OxC, and BLISS are likely O. formigenes strains; BA4 belongs to O. aliiformigenes; and OxCR6 is part of O. paeniformigenes, which has been similarly shown by others (Sidhu et al, 1997;Daniel et al, 2021). Similarly, the data suggested that strain OxCR6 is related to O. paeniformigenes, a relationship that was is supported by the comparable patterns of oxc amplification reported previously (Sidhu et al, 1997).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…While we were not able to sequence the genomes of all Oxalobacter strains, the 16S rRNA gene was used to predict the species that additional strains should be assigned to. These results revealed that SOx4, OxC, and BLISS are likely O. formigenes strains; BA4 belongs to O. aliiformigenes; and OxCR6 is part of O. paeniformigenes, which has been similarly shown by others (Sidhu et al, 1997;Daniel et al, 2021). Similarly, the data suggested that strain OxCR6 is related to O. paeniformigenes, a relationship that was is supported by the comparable patterns of oxc amplification reported previously (Sidhu et al, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Together, these attributes highlight the differences in phage resistance strategies between the species, which could influence their ability to colonize an ecosystem. Given that HOxBLS (O. paraformigenes) was commonly used as a representative strain for group II (Daniel et al, 2021) (Daniel et al, 2021). Given that the oxc gene is critical for metabolism and has been used as a target for genetic identification, we investigated if these genetic differences could alter protein function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, additional analysis of the ratio of urinary oxalate excretion to urinary creatinine excretion showed a significant increase after eight weeks of treatment in the treated group compared with the placebo group. Unfortunately, even though phase II/III clinical trials showed that the 24-week treatment with Oxabact™ OC3 was safe and well-tolerated in patients with primary hyperoxaluria, no effects were noted of the treatment on urinary oxalate levels or on the ratio of urinary oxalate excretion to urinary creatinine excretion [ 67 , 68 , 69 ].…”
Section: Oxalobacter Formigenesmentioning
confidence: 99%